Exercises in Helping Skills A Manual to Accompany Skilled Helper - Egan, Gerard (Broks/Cole Publishing Co, 2007)
Written by Gerard Egan, with assistance from Rich McGourty, this manual parallels the main text, THE SKILLED HELPER, Eighth Edition. The manual allows students to complete self-development exercises as well as practice communication skills and each of the steps of the model in private before using them in actual face-to-face helping interactions with others